A waterproof and breathable composite fabric based on bio-based materials and a preparation method thereof
By using aminosilanized zinc oxide/cellulose nanocrystalline composite materials of bio-based materials and castor oil-based polyurethane in waterproof and moisture-permeable composite fabrics, combined with electrospinning technology, the problem of poor environmental protection in the prior art relying on fluorine-containing materials has been solved, and the improvement of efficient waterproof and moisture-permeable and good antibacterial performance has been achieved.
Patent Information
- Application Number
- CN202411930760.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The waterproof performance of existing waterproof and moisture-permeable composite fabrics mainly relies on fluorine-containing polytetrafluoroethylene microporous membranes, resulting in poor environmental protection and limiting the application of materials.
Using aminosilanized zinc oxide/cellulose nanocrystalline composite materials based on bio-based materials, combined with castor oil-based polyurethane through electrospinning technology to form a composite fabric with excellent waterproof and moisture permeability and antibacterial properties.
It achieves efficient waterproof and moisture-permeable properties and good antibacterial properties. At the same time, the environmental protection of the materials has been improved due to the use of bio-based materials.
Smart Images

Figure CN119348279B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of multi-layer composite fabrics, and in particular to a waterproof and breathable composite fabric based on bio-based materials and a preparation method thereof. Background Art
[0002] Waterproof and breathable composite fabric is a kind of protective textile. It means that water or liquid that exists on the surface of the composite fabric and produces a certain pressure cannot penetrate into the fabric, but the sweat and sweat gas discharged by the human body can be dissipated to the outside in the form of water vapor, and will not accumulate and condense between the skin surface and the fabric.
[0003] The nanofiber membrane obtained by electrospinning has a soft feel due to its ultra-fine fiber diameter. It uses high-voltage static electricity to form a jet of polymer solution, which is split and stretched in the electric field, and finally deposited on the surface of the receiving device as the solvent evaporates, forming a nanofiber membrane with a three-dimensional network structure. The nanofiber membrane has a large specific surface area, high elongation at break and elastic deformation, and high porosity that can improve moisture permeability, and has broad application prospects in the field of waterproof and moisture permeable materials.
[0004] Laminated waterproof and breathable composite fabric refers to a waterproof and breathable composite fabric formed by bonding a functional membrane with waterproof and breathable properties to a fabric using a special composite process, and has outstanding waterproof and breathable properties. Prior art, such as Chinese patent application CN1519106A, discloses a method for preparing a bidirectional elastic polytetrafluoroethylene waterproof and breathable laminated fabric, which is formed by compounding a polytetrafluoroethylene microporous membrane with excellent waterproof and breathable properties with polyurethane to form a bidirectional elastic coating film, and then compounding it with the fabric to form a laminated waterproof and breathable fabric. However, since its waterproof performance is mainly derived from the fluorine-containing polytetrafluoroethylene microporous membrane, although the performance is outstanding, the environmental protection is poor, which limits the application of the material. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a waterproof and breathable composite fabric based on bio-based materials and a preparation method thereof, wherein the composite fabric has excellent waterproof and breathable properties and good antibacterial properties.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a waterproof and breathable composite fabric based on bio-based materials, comprising the following steps:
[0008] Step (1), mixing aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, and N,N-dimethylformamide, adding vanillin cyclocarbonate, reacting, filtering, and drying after the reaction is completed to obtain an antibacterial agent;
[0009] The aminosilanized zinc oxide / cellulose nanocrystal composite material is prepared by the following steps:
[0010] S11, mixing cellulose nanocrystals, sodium hydroxide aqueous solution and ethanol for pretreatment, and after the pretreatment, filtering to obtain pretreated cellulose nanocrystals; mixing the pretreated cellulose nanocrystals with ethanol and stirring to obtain a cellulose nanocrystal dispersion;
[0011] Dissolve zinc acetate dihydrate and ethanol and mix them evenly, add cellulose nanocrystal dispersion dropwise, react after the addition is complete, add a regulator to adjust the pH value, continue the reaction, filter and dry after the reaction is complete, and obtain a zinc oxide / cellulose nanocrystal composite material;
[0012] S12, mixing γ-aminopropyltriethoxysilane with an ethanol aqueous solution, adding a regulator to adjust the pH value, adding the zinc oxide / cellulose nanocrystal composite material, reacting, and after the reaction is completed, standing, centrifuging, and drying to obtain an aminosilanized zinc oxide / cellulose nanocrystal composite material;
[0013] The vanillin-based cyclic carbonate is prepared by the following steps:
[0014] S21, mixing a sodium hydroxide aqueous solution with vanillin, reacting, after the reaction is completed, adding 3-chloro-1,2-propanediol dropwise, after the addition is complete, heating, and continuing the reaction, after the reaction is completed, purifying, and drying to obtain vanillin-based diol;
[0015] S22, mixing vanillin diol, dimethyl carbonate and potassium carbonate, reacting, filtering, washing and drying after the reaction, to obtain vanillin cyclic carbonate;
[0016] Step (2), castor oil-based polyurethane, antibacterial agent, N,N-dimethylacetamide and acetone are mixed and stirred evenly to obtain a spinning solution, and the side of the pretreated polyester fabric with the adhesive is used as a receiving screen, and an electrospinning layer is formed after electrospinning, which is then air-dried and hot-pressed to obtain a waterproof and breathable composite fabric based on bio-based materials.
[0017] Preferably, in step (1), the mass ratio of aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, vanillin cyclocarbonate, and N,N-dimethylformamide is 3:0.19-0.25:1.5-1.8:30-40; and the reaction conditions are: reacting at a temperature of 80-90°C for 24-30h.
[0018] Preferably, when preparing the aminosilanized zinc oxide / cellulose nanocrystal composite material in step (1), in S11: the mass ratio of cellulose nanocrystals, 8-10wt% sodium hydroxide aqueous solution, and ethanol is 2:10-15:5-8, and the sodium hydroxide aqueous solution is 8-10wt% sodium hydroxide aqueous solution; the pretreatment conditions are: pretreatment at room temperature for 0.5-1h; the mass ratio of the pretreated cellulose nanocrystals to ethanol is 1:5-6.
[0019] Preferably, when preparing the aminosilanized zinc oxide / cellulose nanocrystal composite material in step (1), in S11: the mass ratio of zinc acetate dihydrate, ethanol, and cellulose nanocrystal dispersion is 5-7:130-150:100-120; the reaction conditions are: reacting at a temperature of 75-80°C for 40-60min; and the continued reaction conditions are: continuing the reaction at a pH value of 10-11 and a temperature of 75-80°C for 30-60min.
[0020] Preferably, the regulator comprises a 20 wt % sodium hydroxide aqueous solution.
[0021] Preferably, when preparing the aminosilanized zinc oxide / cellulose nanocrystal composite material in step (1), in S12: the mass ratio of γ-aminopropyltriethoxysilane, ethanol aqueous solution, and zinc oxide / cellulose nanocrystal composite material is 0.5-1:250-300:10, and the ethanol aqueous solution is 75 vol% ethanol aqueous solution; the reaction conditions are: stirring the reaction at a pH value of 4-5 and a temperature of 50-60°C for 2-3 hours.
[0022] Preferably, the conditioning agent comprises acetic acid.
[0023] Preferably, when preparing vanillin-based cyclic carbonate in step (1), in S21: the mass ratio of sodium hydroxide aqueous solution to vanillin is 10-12:3, and the sodium hydroxide aqueous solution is 7-8wt% sodium hydroxide aqueous solution; the reaction conditions are: stirring and reacting for 1-2h at 70-80°C in a nitrogen atmosphere; the molar ratio of vanillin and 3-chloro-1,2-propylene glycol is 1:1; the dropwise addition time of 3-chloro-1,2-propylene glycol is 40-60min; and the continued reaction conditions are: continuing the reaction for 4-5h at 90-100°C in a nitrogen atmosphere.
[0024] Preferably, the purification operation comprises: taking the crude reaction product obtained after the reaction is completed, adding 2-3 times the mass of n-butanol of the crude reaction product for extraction, washing with water until neutral, taking the organic phase, removing the solvent by rotary evaporation at a temperature of 80-90°C to obtain a reaction product, sequentially adding 4-5 times the mass of the reaction product ethyl acetate and n-hexane for recrystallization, standing at a temperature of 0-5°C for 1h, filtering, and taking a filter cake.
[0025] Preferably, when preparing vanillin cyclic carbonate in step (1), in S22: the mass ratio of vanillin diol, dimethyl carbonate and potassium carbonate is 20:60-65:0.15-0.18; the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 85-90° C. for 8-9 hours.
[0026] Preferably, in step (2), the mass ratio of castor oil-based polyurethane, antibacterial agent, N,N-dimethylacetamide and acetone is 18-20:0.8-1.2:40-50:50-60; and the hot pressing conditions are: hot pressing at a pressure of 2-3 MPa and a temperature of 90° C. for 2-3 min.
[0027] Preferably, in step (2), the pretreated polyester fabric is prepared by coating an adhesive on one side of the waterproof polyester fabric, wherein the adhesive is coated by spraying and the amount of adhesive applied is 10-14 g / m 2 .
[0028] Preferably, in step (2), the electrospinning operation comprises: loading the spinning solution into a syringe of the electrospinning device, using the side of the pretreated polyester fabric with the adhesive as a receiving screen, and spinning through the electrospinning instrument under the conditions of a temperature of 25-30°C, a liquid discharge rate of 0.15 mm / min, a spinning voltage of 20-25 kV, and a receiving distance of 18 cm.
[0029] Preferably, the castor oil-based polyurethane in step (2) is prepared by the following steps:
[0030] Castor oil, γ-mercaptopropyltrimethoxysilane and photoinitiator benzoin dimethyl ether are mixed and reacted to obtain modified castor oil;
[0031] The mass ratio of castor oil, γ-mercaptopropyltrimethoxysilane and photoinitiator benzoin dimethyl ether is 6.3-6.5:4-4.1:0.3; the reaction conditions are: reacting in an ultraviolet light environment with a wavelength of 365nm for 12-18h;
[0032] isophorone diisocyanate, modified castor oil, and a catalyst dibutyltin dilaurate are mixed and reacted. After the reaction is completed, polycaprolactone diol is added and the reaction is continued. After the reaction is completed, castor oil-based polyurethane is obtained;
[0033] Among them, the mass ratio of isophorone diisocyanate, modified castor oil, catalyst dibutyltin dilaurate, and polycaprolactone diol is 8-10:18-20:0.5-1:12-18; the reaction conditions are: reacting for 2.5-3.5 hours at a temperature of 70-80°C in a nitrogen atmosphere; and the continued reaction conditions are: continuing the reaction for 2-3 hours at a temperature of 75-85°C in a nitrogen atmosphere.
[0034] Preferably, a waterproof and breathable composite fabric based on bio-based materials is prepared by the method for preparing a waterproof and breathable composite fabric based on bio-based materials as described above.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] Cellulose nanocrystal is a cellulose powder material with high crystallinity, large aspect ratio, high modulus and mechanical strength. As a degradable bio-based material, it is introduced into a high molecular polymer to improve the thermal stability and mechanical properties of the material. The present invention uses cellulose nanocrystals as carriers, loads zinc oxide on the surface of cellulose nanocrystals, and then performs surface treatment on the cellulose nanocrystals with γ-aminopropyltriethoxysilane to obtain an aminosilanized zinc oxide / cellulose nanocrystal composite material. The antibacterial properties of the composite material are improved by introducing the inorganic antibacterial agent zinc oxide, while the dispersibility and compatibility of the composite material in the high molecular polymer matrix are improved, and amino functional groups are introduced to provide active sites for subsequent reactions.
[0037] The present invention utilizes the reaction of vanillin and 3-chloro-1,2-propanediol to obtain vanillin-based diol, and then reacts with dimethyl carbonate to close the ring, thereby obtaining vanillin-based cyclic carbonate; by mixing aminosilanized zinc oxide / cellulose nanocrystal composite materials, diethylenetriamine, and vanillin-based cyclic carbonate, two structures of dynamic imine bond (i.e., Schiff base bond) and carbamate bond are formed respectively by utilizing the reaction between amino group and aldehyde group, and between amino group and cyclic carbonate, so that the surface of the zinc oxide / cellulose nanocrystal composite materials is loaded with vanillin-based non-isocyanate polyurethane, not only the compatibility of the composite materials in the polyurethane matrix is further improved by utilizing the similar compatibility principle, but also the antibacterial group Schiff base bond is introduced, which plays a positive addition role on the antibacterial property of the composite materials.
[0038] Castor oil is a bio-based material, the main component of which is fatty acid triglyceride, and the molecular structure contains multiple reactive groups such as hydroxyl and carbon-carbon double bonds, which can replace petroleum-based polyols and be introduced into polyurethane, and improve the comprehensive performance of polyurethane. The present invention introduces a silicon-containing hydrophobic segment by a mercapto-ene click chemical reaction between castor oil and γ-mercaptopropyltrimethoxysilane to obtain a modified castor oil, which is used as an internal crosslinking agent to react with polycaprolactone diol and isophorone diisocyanate, and the silicon-containing hydrophobic segment is introduced into the side chain of the polyurethane, and the obtained castor oil-based polyurethane has better water resistance and comprehensive performance. Castor oil-based polyurethane, an antibacterial agent and a solvent are mixed to prepare a spinning solution, and an electrospinning layer is formed after electrospinning and is laminated with a waterproof polyester fabric through an adhesive, and the obtained composite fabric has excellent waterproof and breathable properties and good antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a process flow chart for preparing a waterproof and breathable composite fabric based on bio-based materials in the present invention;
[0040] Figure 2 Schematic diagram of the structure of the waterproof and breathable composite fabric based on bio-based materials prepared in the present invention;
[0041] Figure 3 is a schematic diagram of the reaction for preparing vanillin-based cyclic carbonate in the present invention;
[0042] Figure 4 It is a bar graph of the antibacterial rate of the composite fabrics prepared in the embodiments and comparative examples of the present invention in the performance test;
[0043] In the figure:
[0044] 1. Electrospinning layer; 2. Adhesive; 3. Pretreated polyester fabric. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] This embodiment discloses a method for preparing a waterproof and breathable composite fabric based on bio-based materials, comprising the following steps:
[0048] Step (1), mixing aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, and N,N-dimethylformamide uniformly, adding vanillin cyclic carbonate, wherein the mass ratio of aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, vanillin cyclic carbonate, and N,N-dimethylformamide is 3:0.19:1.5:30, reacting at 80°C for 30h, filtering after the reaction, taking the filter cake, and drying at 60°C for 12h to obtain an antibacterial agent;
[0049] The aminosilanized zinc oxide / cellulose nanocrystal composite material is prepared by the following steps:
[0050] S11, mixing cellulose nanocrystals, 10 wt% sodium hydroxide aqueous solution, and ethanol in a mass ratio of 2:13:6, pre-treating at room temperature for 1 hour, and after the pre-treatment, filtering and taking the filter cake to obtain pre-treated cellulose nanocrystals; mixing the pre-treated cellulose nanocrystals with ethanol in a mass ratio of 1:5 and stirring for 15 minutes to obtain a cellulose nanocrystal dispersion;
[0051] Dissolve zinc acetate dihydrate and ethanol at 75°C and mix them uniformly, add cellulose nanocrystal dispersion dropwise, the mass ratio of zinc acetate dihydrate, ethanol and cellulose nanocrystal dispersion is 6:140:110, the dropping time is 10min, react at 75°C for 60min after the dropping is completed, add 20wt% sodium hydroxide aqueous solution after the reaction is completed to adjust the pH value to 10, continue to react at 75°C for 60min, filter after the reaction is completed, take the filter cake, and dry at 75°C for 8h to obtain a zinc oxide / cellulose nanocrystal composite material;
[0052] S12, mixing γ-aminopropyltriethoxysilane with 75 vol% ethanol aqueous solution, adding acetic acid to adjust the pH value to 4.5, adding zinc oxide / cellulose nanocrystal composite material, the mass ratio of γ-aminopropyltriethoxysilane, 75 vol% ethanol aqueous solution, and zinc oxide / cellulose nanocrystal composite material is 0.8:280:10, stirring and reacting at 55°C for 2h, after the reaction is completed, standing for 10min, centrifuging, taking the centrifugal precipitate, and drying it at 100°C for 20min to obtain aminosilanized zinc oxide / cellulose nanocrystal composite material;
[0053] The vanillin-based cyclic carbonate is prepared by the following steps:
[0054] S21, a 7wt% sodium hydroxide aqueous solution and vanillin were mixed in a mass ratio of 12:3, stirred and reacted for 2h in a nitrogen atmosphere at 70°C, after the reaction was completed, 3-chloro-1,2-propylene glycol was added dropwise, the molar ratio of vanillin and 3-chloro-1,2-propylene glycol was 1:1, and the dropping time was 40min. After the dropping was completed, the temperature was raised, and the reaction was continued for 5h in a nitrogen atmosphere at 90°C. After the reaction was completed, a crude reaction product was obtained, and n-butanol twice the mass of the crude reaction product was added for extraction, washed with water until neutral, the organic phase was taken, and the solvent was removed by rotary evaporation at 80°C to obtain a reaction product, ethyl acetate and n-hexane four times the mass of the reaction product were added in sequence for recrystallization, and the mixture was allowed to stand at 0°C for 1h, filtered, the filter cake was taken, and dried at 50°C for 10h to obtain vanillin-based diol;
[0055] S22, vanillin diol, dimethyl carbonate, and potassium carbonate were mixed in a mass ratio of 20:60:0.15, and reacted in a nitrogen atmosphere at 85° C. for 9 hours. After the reaction was completed, the mixture was filtered, the filter cake was taken, and ethanol 5 times the mass of the filter cake was added for washing, and the mixture was dried at 50° C. for 18 hours to obtain vanillin cyclic carbonate;
[0056] Step (2), mixing castor oil-based polyurethane, antibacterial agent, N,N-dimethylacetamide, and acetone at a mass ratio of 18:0.8:40:60 at a temperature of 50° C. and stirring to obtain a spinning solution, loading the spinning solution into a syringe of an electrospinning device, using the side of the pretreated polyester fabric with the adhesive as a receiving screen, spinning through an electrospinning instrument under the conditions of a temperature of 25° C., a liquid discharge rate of 0.15 mm / min, a spinning voltage of 20 kV, and a receiving distance of 18 cm, forming an electrospinning layer after spinning, laying it flat and drying it until the solvent is completely evaporated, and hot pressing it at a pressure of 2 MPa and a temperature of 90° C. for 2 minutes to obtain a waterproof and breathable composite fabric based on bio-based materials;
[0057] The pretreated polyester fabric is prepared by coating adhesive on one side of the waterproof polyester fabric, wherein the adhesive coating method is spraying method, and the amount of adhesive applied is 10g / m 2 ;
[0058] Castor oil-based polyurethane is prepared by the following steps:
[0059] Castor oil, γ-mercaptopropyltrimethoxysilane and photoinitiator benzoin dimethyl ether were mixed in a nitrogen atmosphere at a mass ratio of 6.3:4:0.3, and reacted in an ultraviolet light environment with a wavelength of 365 nm for 12 hours. After the reaction was completed, modified castor oil was obtained;
[0060] Isophorone diisocyanate, modified castor oil, and catalyst dibutyltin dilaurate were mixed, reacted in a nitrogen atmosphere at 70°C for 3.5 hours. After the reaction, polycaprolactone diol was added. The mass ratio of isophorone diisocyanate, modified castor oil, catalyst dibutyltin dilaurate, and polycaprolactone diol was 8:18:0.5:12. The reaction was continued at 75°C for 3 hours. After the reaction, castor oil-based polyurethane was obtained.
[0061] Example 2
[0062] This embodiment discloses a method for preparing a waterproof and breathable composite fabric based on bio-based materials, comprising the following steps:
[0063] Step (1), mixing aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, and N,N-dimethylformamide uniformly, adding vanillin cyclic carbonate, wherein the mass ratio of aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, vanillin cyclic carbonate, and N,N-dimethylformamide is 3:0.2:1.55:35, reacting at 85°C for 26 hours, filtering after the reaction, taking the filter cake, and drying at 65°C for 10 hours to obtain an antibacterial agent;
[0064] The preparation of aminosilanized zinc oxide / cellulose nanocrystal composite material is the same as that in Example 1;
[0065] The vanillin-based cyclic carbonate is prepared by the following steps:
[0066] A 7wt% sodium hydroxide aqueous solution and vanillin are mixed in a mass ratio of 12:3, stirred and reacted for 2h in a nitrogen atmosphere at 70°C, after the reaction, 3-chloro-1,2-propylene glycol is added dropwise, the molar ratio of vanillin and 3-chloro-1,2-propylene glycol is 1:1, and the dropping time is 45min. After the dropping is completed, the temperature is raised, and the reaction is continued for 5h in a nitrogen atmosphere at 90°C. After the reaction is completed, a crude reaction product is obtained, and n-butanol twice the mass of the crude reaction product is added for extraction, washed with water until neutral, and the organic phase is taken, and the solvent is removed by rotary evaporation at 80°C to obtain a reaction product, and ethyl acetate and n-hexane four times the mass of the reaction product are added in sequence for recrystallization, and the mixture is allowed to stand at 0°C for 1h, filtered, and the filter cake is taken and dried at 50°C for 10h to obtain vanillin-based diol;
[0067] Vanillin diol, dimethyl carbonate and potassium carbonate were mixed in a mass ratio of 20:62:0.16, and reacted at 85°C for 9 hours in a nitrogen atmosphere. After the reaction was completed, the mixture was filtered, the filter cake was taken, and ethanol 6 times the mass of the filter cake was added for washing, and the mixture was dried at 55°C for 15 hours to obtain vanillin cyclic carbonate;
[0068] Step (2), mixing castor oil-based polyurethane, antibacterial agent, N,N-dimethylacetamide, and acetone at a mass ratio of 18.5:0.9:45:55 at a temperature of 55° C. and stirring uniformly to obtain a spinning solution, loading the spinning solution into a syringe of an electrospinning device, using the side of the pretreated polyester fabric with the adhesive as a receiving screen, spinning through an electrospinning instrument under the conditions of a temperature of 28° C., a liquid discharge rate of 0.15 mm / min, a spinning voltage of 20 kV, and a receiving distance of 18 cm, forming an electrospinning layer after spinning, laying it flat to dry until the solvent is completely evaporated, and hot pressing it at a pressure of 2 MPa and a temperature of 90° C. for 2 minutes to obtain a waterproof and breathable composite fabric based on bio-based materials;
[0069] The pretreated polyester fabric is prepared by coating adhesive on one side of the waterproof polyester fabric, wherein the adhesive coating method is spraying, and the amount of adhesive applied is 12g / m 2 ;
[0070] Castor oil-based polyurethane is prepared by the following steps:
[0071] Castor oil, γ-mercaptopropyltrimethoxysilane and photoinitiator benzoin dimethyl ether were mixed in a nitrogen atmosphere at a mass ratio of 6.35:4:0.3, and reacted in an ultraviolet light environment with a wavelength of 365 nm for 16 hours. After the reaction was completed, modified castor oil was obtained;
[0072] Isophorone diisocyanate, modified castor oil and catalyst dibutyltin dilaurate were mixed and reacted in a nitrogen atmosphere at 70°C for 3 hours. After the reaction, polycaprolactone diol was added. The mass ratio of isophorone diisocyanate, modified castor oil, catalyst dibutyltin dilaurate and polycaprolactone diol was 8.5:18.5:0.8:13. The reaction was continued at 80°C for 2.5 hours. After the reaction, castor oil-based polyurethane was obtained.
[0073] Example 3
[0074] This embodiment discloses a method for preparing a waterproof and breathable composite fabric based on bio-based materials, comprising the following steps:
[0075] Step (1), mixing aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, and N,N-dimethylformamide uniformly, adding vanillin cyclic carbonate, wherein the mass ratio of aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, vanillin cyclic carbonate, and N,N-dimethylformamide is 3:0.22:1.6:35, reacting at 85°C for 26 hours, filtering after the reaction, taking the filter cake, and drying at 65°C for 10 hours to obtain an antibacterial agent;
[0076] The preparation of aminosilanized zinc oxide / cellulose nanocrystal composite material is the same as that in Example 1;
[0077] The vanillin-based cyclic carbonate is prepared by the following steps:
[0078] 8 wt % sodium hydroxide aqueous solution and vanillin were mixed in a mass ratio of 11:3, stirred and reacted for 1.5 h in a nitrogen atmosphere at 75°C, and after the reaction, 3-chloro-1,2-propylene glycol was added dropwise, the molar ratio of vanillin and 3-chloro-1,2-propylene glycol was 1:1, and the dropping time was 45 min. After the dropping was completed, the temperature was raised, and the reaction was continued for 4.5 h in a nitrogen atmosphere at 95°C. After the reaction was completed, a crude reaction product was obtained, and n-butanol twice the mass of the crude reaction product was added for extraction, washed with water until neutral, and the organic phase was taken. The solvent was removed by rotary evaporation at 80°C to obtain a reaction product, and ethyl acetate and n-hexane four times the mass of the reaction product were added in sequence for recrystallization, and the mixture was allowed to stand at 0°C for 1 h, filtered, and the filter cake was taken and dried at 50°C for 10 h to obtain vanillin-based diol;
[0079] Vanillin diol, dimethyl carbonate and potassium carbonate were mixed in a mass ratio of 20:63:0.16, and reacted at 85°C for 9 hours in a nitrogen atmosphere. After the reaction was completed, the mixture was filtered, the filter cake was taken, and ethanol 6 times the mass of the filter cake was added for washing, and the mixture was dried at 55°C for 15 hours to obtain vanillin cyclic carbonate;
[0080] Step (2), mixing castor oil-based polyurethane, antibacterial agent, N,N-dimethylacetamide, and acetone at a mass ratio of 19:1:45:55 at a temperature of 55° C. and stirring uniformly to obtain a spinning solution, loading the spinning solution into a syringe of an electrospinning device, using the side of the pretreated polyester fabric with the adhesive as a receiving screen, spinning through an electrospinning instrument under the conditions of a temperature of 28° C., a liquid discharge rate of 0.15 mm / min, a spinning voltage of 23 kV, and a receiving distance of 18 cm, forming an electrospinning layer after spinning, laying it flat and drying it until the solvent is completely evaporated, and hot pressing it at a pressure of 2.5 MPa and a temperature of 90° C. for 2.5 min to obtain a waterproof and breathable composite fabric based on bio-based materials;
[0081] The pretreated polyester fabric is prepared by coating adhesive on one side of the waterproof polyester fabric, wherein the adhesive coating method is spraying, and the amount of adhesive applied is 12g / m 2 ;
[0082] Castor oil-based polyurethane is prepared by the following steps:
[0083] Castor oil, γ-mercaptopropyltrimethoxysilane and photoinitiator benzoin dimethyl ether were mixed in a nitrogen atmosphere at a mass ratio of 6.4:4.05:0.3, and reacted in an ultraviolet light environment with a wavelength of 365 nm for 16 hours. After the reaction was completed, modified castor oil was obtained;
[0084] Isophorone diisocyanate, modified castor oil, and catalyst dibutyltin dilaurate were mixed, reacted in a nitrogen atmosphere at 75°C for 3 hours. After the reaction, polycaprolactone diol was added. The mass ratio of isophorone diisocyanate, modified castor oil, catalyst dibutyltin dilaurate, and polycaprolactone diol was 9:19:0.8:15. The reaction was continued at 80°C for 2.5 hours. After the reaction, castor oil-based polyurethane was obtained.
[0085] Example 4
[0086] This embodiment discloses a method for preparing a waterproof and breathable composite fabric based on bio-based materials, comprising the following steps:
[0087] Step (1), mixing aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, and N,N-dimethylformamide uniformly, adding vanillin cyclic carbonate, wherein the mass ratio of aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, vanillin cyclic carbonate, and N,N-dimethylformamide is 3:0.24:1.7:35, reacting at 85°C for 26 hours, filtering after the reaction, taking the filter cake, and drying at 70°C for 8 hours to obtain an antibacterial agent;
[0088] The preparation of aminosilanized zinc oxide / cellulose nanocrystal composite material is the same as that in Example 1;
[0089] The vanillin-based cyclic carbonate is prepared by the following steps:
[0090] 8 wt % sodium hydroxide aqueous solution and vanillin are mixed in a mass ratio of 11:3, stirred and reacted at 80° C. in a nitrogen atmosphere for 1 h, and after the reaction is completed, 3-chloro-1,2-propylene glycol is added dropwise, the molar ratio of vanillin and 3-chloro-1,2-propylene glycol is 1:1, and the dropping time is 45 min. After the dropping is completed, the temperature is raised, and the reaction is continued for 4.5 h in a nitrogen atmosphere at 100° C. After the reaction is completed, a crude reaction product is obtained, and n-butanol twice the mass of the crude reaction product is added for extraction, washed with water until neutral, and the organic phase is taken, and the solvent is removed by rotary evaporation at 80° C. to obtain a reaction product, and ethyl acetate and n-hexane four times the mass of the reaction product are added in sequence for recrystallization, and the mixture is allowed to stand at 0° C. for 1 h, filtered, and the filter cake is taken and dried at 50° C. for 10 h to obtain vanillin-based diol;
[0091] Vanillin diol, dimethyl carbonate and potassium carbonate were mixed in a mass ratio of 20:64:0.16, reacted in a nitrogen atmosphere at 90°C for 8 hours, filtered, and the filter cake was taken after the reaction was completed. Ethanol 6 times the mass of the filter cake was added for washing, and dried at 55°C for 15 hours to obtain vanillin cyclic carbonate;
[0092] Step (2), mixing castor oil-based polyurethane, antibacterial agent, N,N-dimethylacetamide, and acetone at a mass ratio of 19.5:1.1:45:55 at a temperature of 55° C. and stirring evenly to obtain a spinning solution, loading the spinning solution into a syringe of an electrospinning device, using the side of the pretreated polyester fabric with the adhesive as a receiving screen, spinning through an electrospinning instrument under the conditions of a temperature of 30° C., a liquid discharge rate of 0.15 mm / min, a spinning voltage of 23 kV, and a receiving distance of 18 cm, forming an electrospinning layer after spinning, laying it flat and drying it until the solvent is completely evaporated, and hot pressing it at a pressure of 2.5 MPa and a temperature of 90° C. for 3 minutes to obtain a waterproof and breathable composite fabric based on bio-based materials;
[0093] The pretreated polyester fabric is prepared by coating adhesive on one side of the waterproof polyester fabric, wherein the adhesive coating method is spraying method, and the amount of adhesive applied is 12g / m 2 ;
[0094] Castor oil-based polyurethane is prepared by the following steps:
[0095] Castor oil, γ-mercaptopropyltrimethoxysilane and photoinitiator benzoin dimethyl ether were mixed in a nitrogen atmosphere at a mass ratio of 6.45:4.1:0.3, and reacted in an ultraviolet light environment with a wavelength of 365 nm for 16 hours. After the reaction was completed, modified castor oil was obtained;
[0096] Isophorone diisocyanate, modified castor oil, and catalyst dibutyltin dilaurate were mixed, reacted in a nitrogen atmosphere at 75°C for 3 hours, and after the reaction, polycaprolactone diol was added. The mass ratio of isophorone diisocyanate, modified castor oil, catalyst dibutyltin dilaurate, and polycaprolactone diol was 9.5:19.5:0.8:16, and the reaction was continued at 80°C for 2.5 hours. After the reaction, castor oil-based polyurethane was obtained.
[0097] Example 5
[0098] This embodiment discloses a method for preparing a waterproof and breathable composite fabric based on bio-based materials, comprising the following steps:
[0099] Step (1), mixing aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, and N,N-dimethylformamide uniformly, adding vanillin cyclic carbonate, wherein the mass ratio of aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, vanillin cyclic carbonate, and N,N-dimethylformamide is 3:0.25:1.8:40, reacting at 90°C for 24h, filtering after the reaction, taking the filter cake, and drying at 70°C for 8h to obtain an antibacterial agent;
[0100] The preparation of aminosilanized zinc oxide / cellulose nanocrystal composite material is the same as that in Example 1;
[0101] The vanillin-based cyclic carbonate is prepared by the following steps:
[0102] 8 wt % sodium hydroxide aqueous solution and vanillin are mixed in a mass ratio of 10:3, stirred and reacted for 1 hour in a nitrogen atmosphere at 80°C, and after the reaction is completed, 3-chloro-1,2-propylene glycol is added dropwise, the molar ratio of vanillin and 3-chloro-1,2-propylene glycol is 1:1, and the dropping time is 60 minutes. After the dropping is completed, the temperature is raised, and the reaction is continued for 4 hours in a nitrogen atmosphere at 100°C. After the reaction is completed, a crude reaction product is obtained, and n-butanol 3 times the mass of the crude reaction product is added for extraction, washed with water until neutral, and the organic phase is taken, and the solvent is removed by rotary evaporation at 90°C to obtain a reaction product, and ethyl acetate and n-hexane 5 times the mass of the reaction product are added in sequence for recrystallization, and the mixture is allowed to stand at 5°C for 1 hour, filtered, and the filter cake is taken and dried at 60°C for 8 hours to obtain vanillin-based diol;
[0103] Vanillin diol, dimethyl carbonate and potassium carbonate were mixed in a mass ratio of 20:65:0.18, reacted in a nitrogen atmosphere at 90°C for 8 hours, filtered, and the filter cake was taken after the reaction was completed, and ethanol 8 times the mass of the filter cake was added for washing, and dried at 60°C for 12 hours to obtain vanillin cyclic carbonate;
[0104] Step (2), mixing castor oil-based polyurethane, antibacterial agent, N,N-dimethylacetamide, and acetone at a mass ratio of 20:1.2:50:50 at a temperature of 60° C. and stirring to obtain a spinning solution, loading the spinning solution into a syringe of an electrospinning device, using the side of the pretreated polyester fabric with the adhesive as a receiving screen, spinning through an electrospinning instrument under the conditions of a temperature of 30° C., a liquid discharge rate of 0.15 mm / min, a spinning voltage of 25 kV, and a receiving distance of 18 cm, forming an electrospinning layer after spinning, laying it flat and drying it until the solvent is completely evaporated, and hot pressing it at a pressure of 3 MPa and a temperature of 90° C. for 3 minutes to obtain a waterproof and breathable composite fabric based on bio-based materials;
[0105] The pretreated polyester fabric is prepared by coating adhesive on one side of the waterproof polyester fabric, wherein the adhesive coating method is spraying method, and the amount of adhesive applied is 14g / m 2 ;
[0106] Castor oil-based polyurethane is prepared by the following steps:
[0107] Castor oil, γ-mercaptopropyltrimethoxysilane and photoinitiator benzoin dimethyl ether were mixed in a nitrogen atmosphere at a mass ratio of 6.5:4.1:0.3, and reacted in an ultraviolet light environment with a wavelength of 365 nm for 18 hours. After the reaction was completed, modified castor oil was obtained;
[0108] Isophorone diisocyanate, modified castor oil, and catalyst dibutyltin dilaurate were mixed, reacted in a nitrogen atmosphere at 80°C for 2.5 hours. After the reaction, polycaprolactone diol was added. The mass ratio of isophorone diisocyanate, modified castor oil, catalyst dibutyltin dilaurate, and polycaprolactone diol was 10:20:1:18. The reaction was continued at 85°C for 2 hours. After the reaction, castor oil-based polyurethane was obtained.
[0109] Comparative Example 1
[0110] This comparative example discloses a method for preparing a composite fabric, comprising the following steps:
[0111] Castor oil-based polyurethane, zinc oxide / cellulose nanocrystal composite material, N,N-dimethylacetamide, and acetone were mixed and stirred at a mass ratio of 18:0.8:40:60 at a temperature of 50°C to obtain a spinning solution, and the spinning solution was loaded into a syringe of an electrospinning device. The side of the pretreated polyester fabric with the adhesive was used as a receiving screen, and the spinning was performed by an electrospinning instrument under the conditions of a temperature of 25°C, a liquid discharge rate of 0.15 mm / min, a spinning voltage of 20 kV, and a receiving distance of 18 cm. After the spinning was completed, an electrospinning layer was formed, which was flattened and dried until the solvent was completely evaporated, and hot pressed at a pressure of 2 MPa and a temperature of 90°C for 2 minutes to obtain a composite fabric;
[0112] The pretreated polyester fabric is prepared by coating adhesive on one side of the waterproof polyester fabric, wherein the adhesive coating method is spraying method, and the amount of adhesive applied is 10g / m 2 ;
[0113] Castor oil-based polyurethane is prepared by the following steps:
[0114] Castor oil, γ-mercaptopropyltrimethoxysilane and photoinitiator benzoin dimethyl ether were mixed in a nitrogen atmosphere at a mass ratio of 6.3:4:0.3, and reacted in an ultraviolet light environment with a wavelength of 365 nm for 12 hours. After the reaction was completed, modified castor oil was obtained;
[0115] Isophorone diisocyanate, modified castor oil, and catalyst dibutyltin dilaurate were mixed, reacted in a nitrogen atmosphere at 70°C for 3.5 hours. After the reaction, polycaprolactone diol was added. The mass ratio of isophorone diisocyanate, modified castor oil, catalyst dibutyltin dilaurate, and polycaprolactone diol was 8:18:0.5:12. The reaction was continued at 75°C for 3 hours. After the reaction, castor oil-based polyurethane was obtained.
[0116] Comparative Example 2
[0117] This comparative example discloses a method for preparing a composite fabric, comprising the following steps:
[0118] Step (1), mixing aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, and N,N-dimethylformamide uniformly, adding vanillin cyclic carbonate, wherein the mass ratio of aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine, vanillin cyclic carbonate, and N,N-dimethylformamide is 3:0.19:1.5:30, reacting at 80°C for 30h, filtering after the reaction, taking the filter cake, and drying at 60°C for 12h to obtain an antibacterial agent;
[0119] The preparation of aminosilanized zinc oxide / cellulose nanocrystal composite material is the same as that in Example 1;
[0120] The vanillin-based cyclic carbonate is prepared by the following steps:
[0121] A 7wt% sodium hydroxide aqueous solution and vanillin are mixed in a mass ratio of 12:3, stirred and reacted for 2h in a nitrogen atmosphere at 70°C, after the reaction is completed, 3-chloro-1,2-propylene glycol is added dropwise, the molar ratio of vanillin and 3-chloro-1,2-propylene glycol is 1:1, and the dropping time is 40min. After the dropping is completed, the temperature is raised, and the reaction is continued for 5h in a nitrogen atmosphere at 90°C. After the reaction is completed, a crude reaction product is obtained, and n-butanol twice the mass of the crude reaction product is added for extraction, washed with water until neutral, and the organic phase is taken, and the solvent is removed by rotary evaporation at 80°C to obtain a reaction product, and ethyl acetate and n-hexane four times the mass of the reaction product are added in sequence for recrystallization, and the mixture is allowed to stand at 0°C for 1h, filtered, and the filter cake is taken and dried at 50°C for 10h to obtain vanillin-based diol;
[0122] Vanillin diol, dimethyl carbonate and potassium carbonate were mixed in a mass ratio of 20:60:0.15, reacted in a nitrogen atmosphere at 85°C for 9 hours, filtered, and the filter cake was taken after the reaction was completed. Ethanol 5 times the mass of the filter cake was added for washing, and dried at 50°C for 18 hours to obtain vanillin cyclic carbonate;
[0123] Step (2), mixing polyurethane, antibacterial agent, N,N-dimethylacetamide and acetone at a mass ratio of 18:0.8:40:60 at a temperature of 50°C and stirring evenly to obtain a spinning solution, loading the spinning solution into a syringe of an electrospinning device, using the side of the pretreated polyester fabric with the adhesive as a receiving screen, spinning through an electrospinning instrument under the conditions of a temperature of 25°C, a liquid discharge rate of 0.15 mm / min, a spinning voltage of 20 kV, and a receiving distance of 18 cm, forming an electrospinning layer after spinning, laying it flat and drying it until the solvent is completely evaporated, and hot pressing it at a pressure of 2 MPa and a temperature of 90°C for 2 minutes to obtain a composite fabric;
[0124] The pretreated polyester fabric is prepared by coating adhesive on one side of the polyester fabric, wherein the adhesive coating method is spraying method, and the amount of adhesive applied is 10g / m 2 ;
[0125] Polyurethane is prepared by the following steps:
[0126] Isophorone diisocyanate, polycaprolactone diol, and catalyst dibutyltin dilaurate were mixed in a mass ratio of 8:30:0.5, and reacted at 70° C. for 6.5 hours in a nitrogen atmosphere. After the reaction was completed, polyurethane was obtained.
[0127] In the above embodiments and comparative examples: the polyester fabric is commercially available with a gram weight of 140 g / m 2 Polyester woven fabric; waterproof polyester fabric is commercially available with a weight of 140g / m 2 The polyester woven fabric is made after waterproof finishing, and the finishing process includes: impregnating the polyester woven fabric with a waterproof finishing agent, the bath ratio is 1:50, the impregnation time is 20 minutes, one immersion and one rolling, the rolling rate is 75-82%, after impregnation, drying at 100°C for 4 minutes, and baking at 150°C for 2 minutes; in the waterproof finishing agent, the water repellent concentration is 40g / L, and the specification is RUCO-DRY ECO brand fluorine-free waterproofing agent; the concentration of penetrant and cross-linking agent is 10g / L, and the specifications are all commercially available; cellulose nanocrystals are from Tianjin Xidian Chemical Technology Co., Ltd., chemically pure, CAS number: 9004-34-6; zinc acetate dihydrate is from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., CAS number: 5970-45-6; γ-aminopropyl triethoxysilane is from Shandong Guohua Chemical Co., Ltd., CAS number: 919-30-2; vanillin is from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number: 121-33-5; 3-chloro-1,2-propanediol is from Shandong Polychemical Co., Ltd., CAS No.: 96-24-2; dimethyl carbonate comes from Shanghai MacLean Biochemical Technology Co., Ltd., CAS No.: 616-38-6; the adhesive is a moisture-curing polyurethane adhesive from Shandong Shoucheng Chemical Co., Ltd., item No. HT-320; castor oil comes from Shanghai Aladdin Biochemical Technology Co., Ltd., specification chemically pure, CAS No.: 8001-79-4; γ-mercaptopropyltrimethoxysilane comes from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 4420-74-0; polycaprolactone diol comes from Jiangsu Haolong Chemical Co., Ltd., specification PCL-1000.
[0128] Test example
[0129] The performance of the composite fabrics prepared in the examples and comparative examples was tested, and the specific results are shown in Table 1:
[0130] Table 1
[0131]
[0132] Among the indicators in Table 1: hydrostatic pressure is measured with reference to GB / T 4744-2013 "Testing and evaluation of waterproof performance of textiles"; moisture permeability is measured with reference to GB / T 12704-2009 "Test method for moisture permeability of textile fabrics Part 1: Moisture absorption method"; antibacterial rate is measured with reference to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", and Escherichia coli is selected as the bacterial species.
[0133] It can be seen from the test results in Table 1 that the composite fabric prepared by the present invention has excellent waterproof and moisture permeability and good antibacterial performance.
[0134] The present invention uses the reaction between amino group and aldehyde group, amino group and cyclic carbonate to react aminosilanized zinc oxide / cellulose nanocrystal composite material, diethylenetriamine and vanillin cyclic carbonate to form two structures of dynamic imine bond (i.e. Schiff base bond) and carbamate bond, so that the surface of zinc oxide / cellulose nanocrystal composite material is loaded with vanillin non-isocyanate polyurethane, not only further improves the compatibility of composite material in polyurethane matrix by similar compatibility principle, but also introduces antibacterial group Schiff base bond, which plays a positive addition role in the antibacterial property of composite material. In comparative example 1, the zinc oxide / cellulose nanocrystal composite material of electrospinning layer has no surface modification, the compatibility of zinc oxide / cellulose nanocrystal composite material with polyurethane matrix is reduced, it is easy to agglomerate, and lacks organic antibacterial agent group, so the antibacterial property of comparative example 1 is lower than that of the embodiment.
[0135] The present invention prepares a hydrophobic modified castor oil, uses it as an internal crosslinking agent to react with polycaprolactone diol and isophorone diisocyanate, and introduces a silicon-containing hydrophobic segment into the side chain of the polyurethane, so that the obtained castor oil-based polyurethane has better water resistance and comprehensive performance. In Comparative Example 2, the electrospinning layer does not add modified castor oil, and no waterproof treatment is performed when preparing the pretreated polyester fabric, so the waterproof and water-resistant performance of the composite fabric is reduced, so the waterproof performance of Comparative Example 2 is lower than that of the embodiment.
[0136] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a waterproof and breathable composite fabric based on bio-based materials, characterized in that: The following steps are involved: Step (1), by weight, 3 parts of aminosilanized zinc oxide / cellulose nanocrystal composite material, 0.19-0.25 parts of diethylenetriamine, and 30-40 parts of N,N-dimethylformamide are mixed evenly, and 1.5-1.8 parts of vanillin cyclocarbonate are added, and reacted. After the reaction is completed, the mixture is filtered and dried to obtain an antibacterial agent; Step (2), by weight, 6.3-6.5 parts of castor oil, 4-4.1 parts of γ-mercaptopropyltrimethoxysilane, and 0.3 parts of photoinitiator benzoin dimethyl ether are mixed, and reacted in an ultraviolet light environment with a wavelength of 365 nm for 12-18 hours. After the reaction is completed, modified castor oil is obtained; 8-10 parts of isophorone diisocyanate, 18-20 parts of modified castor oil, and 0.5-1 parts of dibutyltin dilaurate as a catalyst are mixed and reacted. After the reaction is completed, 12-18 parts of polycaprolactone diol are added and the reaction is continued. After the reaction is completed, castor oil-based polyurethane is obtained; The polyester woven fabric is waterproofed to obtain a waterproof polyester fabric; an adhesive is applied on one side of the waterproof polyester fabric to obtain a pretreated polyester fabric; 18-20 parts of castor oil-based polyurethane, 0.8-1.2 parts of an antibacterial agent, 40-50 parts of N,N-dimethylacetamide, and 50-60 parts of acetone are mixed and stirred evenly to obtain a spinning solution; the side of the pretreated polyester fabric with the adhesive is used as a receiving screen, electrostatic spinning is performed, and hot pressing is performed to obtain a waterproof and breathable composite fabric based on bio-based materials.
2. The method for preparing a waterproof and breathable composite fabric based on bio-based materials according to claim 1, characterized in that: In the step (1): The reaction conditions are: react at 80-90°C for 24-30h.
3. The method for preparing a waterproof and breathable composite fabric based on bio-based materials according to claim 1, characterized in that: The aminosilanized zinc oxide / cellulose nanocrystal composite material in step (1) is prepared by the following steps: S11, mixing 2 parts of cellulose nanocrystals, 10-15 parts of 8-10wt% sodium hydroxide aqueous solution, and 5-8 parts of ethanol, by weight, and pre-treating them. After the pre-treatment, filtering them to obtain pre-treated cellulose nanocrystals; mixing 1 part of the pre-treated cellulose nanocrystals with 5-6 parts of ethanol and stirring them to obtain a cellulose nanocrystal dispersion; Dissolve 5-7 parts of zinc acetate dihydrate and 130-150 parts of ethanol and mix them evenly, add 100-120 parts of cellulose nanocrystal dispersion dropwise, react after the addition is complete, add a regulator to adjust the pH value to 10-11 after the reaction is complete, continue the reaction, filter and dry after the reaction is complete to obtain a zinc oxide / cellulose nanocrystal composite material; S12. Mix 0.5-1 parts of γ-aminopropyltriethoxysilane with 250-300 parts of 75 vol% ethanol aqueous solution, by weight, add a regulator to adjust the pH value, add 10 parts of zinc oxide / cellulose nanocrystal composite material, react, and after the reaction is completed, let stand, centrifuge, and dry to obtain aminosilanized zinc oxide / cellulose nanocrystal composite material.
4. The method for preparing a waterproof and breathable composite fabric based on bio-based materials according to claim 3, characterized in that: When preparing the aminosilanized zinc oxide / cellulose nanocrystal composite material: In S11, the pretreatment conditions are: pretreatment at room temperature for 0.5-1h; the reaction conditions are: reaction at 75-80°C for 40-60min; the continued reaction conditions are: continued reaction at 75-80°C for 30-60min; In S12: the reaction conditions are: stirring the reaction at a pH of 4-5 and a temperature of 50-60°C for 2-3h.
5. The method for preparing a waterproof and breathable composite fabric based on bio-based materials according to claim 1, characterized in that: The vanillin-based cyclic carbonate in step (1) is prepared by the following steps: S21, mixing 10-12 parts of a 7-8 wt% sodium hydroxide aqueous solution with 3 parts of vanillin by weight, reacting, and after the reaction, adding 3-chloro-1,2-propylene glycol dropwise, with the molar ratio of vanillin to 3-chloro-1,2-propylene glycol being 1:
1. After the addition is complete, heating is increased, and the reaction is continued. After the reaction is complete, purification and drying are performed to obtain vanillin-based diol; S22. Mix 20 parts of vanillin diol, 60-65 parts of dimethyl carbonate and 0.15-0.18 parts of potassium carbonate by mass, and react. After the reaction is completed, filter, wash and dry to obtain vanillin cyclic carbonate.
6. The method for preparing a waterproof and breathable composite fabric based on bio-based materials according to claim 5, characterized in that: When preparing the vanillin-based cyclic carbonate: In S21, the reaction conditions are: stirring the reaction at 70-80°C in a nitrogen atmosphere for 1-2 hours; the dropwise addition time of 3-chloro-1,2-propanediol is 40-60 minutes; the continued reaction conditions are: continuing the reaction at 90-100°C in a nitrogen atmosphere for 4-5 hours; In S22: the reaction conditions are: reacting in a nitrogen atmosphere at 85-90°C for 8-9h.
7. The method for preparing a waterproof and breathable composite fabric based on bio-based materials according to claim 1, characterized in that: In step (2): The hot pressing conditions are: hot pressing at a pressure of 2-3Mpa and a temperature of 90°C for 2-3min; the adhesive coating method is spraying, and the amount of glue applied is 10-14g / m 2 ; The electrospinning operation includes: loading the spinning solution into the syringe of the electrospinning equipment, using the side of the pretreated polyester fabric with the adhesive as the receiving screen, spinning through the electrospinning instrument under the conditions of a temperature of 25-30°C, a liquid discharge rate of 0.15 mm / min, a spinning voltage of 20-25kV, and a receiving distance of 18cm. After the spinning is completed, an electrospinning layer is formed, which is spread flat and dried until the solvent is completely evaporated.
8. The method for preparing a waterproof and breathable composite fabric based on bio-based materials according to claim 1, characterized in that: In the step (2), when preparing castor oil-based polyurethane: The reaction conditions are: reacting in a nitrogen atmosphere at 70-80°C for 2.5-3.5 hours; the continued reaction conditions are: continuing the reaction in a nitrogen atmosphere at 75-85°C for 2-3 hours.
9. A waterproof and breathable composite fabric based on bio-based materials prepared by the method for preparing a waterproof and breathable composite fabric based on bio-based materials as claimed in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing laminated textile with waterproof and transmission of humidity made from bi-directiona elastic Teflon
CN1519106A
Method for manufacturing zinc oxide-cellulose nanocrystalline composite fiber film with antibacterial characteristic and photocatalytic degradation characteristic at same time
CN104018235A
Antibacterial disinfection nanofiber medical dressing and preparation method thereof
CN112972750A